Peran Guru IPS dalam Mengimplementasian Nilai-Nilai Pancasila pada Mata Pelajaran IPS Kelas Vll di MTS Negeri 2 Jombang - Muhammad Azril Rakhmatulloh; Yudi Krisno Wicaksono (Jurnal Sadewa : Publikasi Ilmu Pendidikan, Pembelajaran dan Ilmu Sosial, 2025)
This study aims to examine the role of Social Studies (IPS) teachers in implementing Pancasila values in Social Studies learning for eighth-grade students at MTs Negeri 2 Jombang. A qualitative descriptive approach was used, with data collected through observation, interviews, and documentation. The research subjects consisted of Social Studies teachers and eighth-grade students. The results showed that the implementation of Pancasila values was carried out by integrating values such as tolerance, mutual cooperation, and social justice into Social Studies learning and students' daily interactions. Strategies included regular religious activities, moral messaging, and exemplary behavior by teachers. This implementation positively impacted character development, reduced bullying behavior, and increased awareness of diversity and unity. Challenges included students' diverse backgrounds and limited instructional time. These findings indicate that Social Studies teachers play a central role in instilling Pancasila values to shape students into individuals with strong character and a sense of national identity.